2014
DOI: 10.1371/journal.pone.0109103
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Programmed Death-1 Homologue-1 (PD-1H) Expression and Function in Normal and HIV Infected Individuals

Abstract: Chronic immune activation that persists despite anti-retroviral therapy (ART) is the strongest predictor of disease progression in HIV infection. Monocyte/macrophages in HIV-infected individuals are known to spontaneously secrete cytokines, although neither the mechanism nor the molecules involved are known. Here we show that overexpression of the newly described co-stimulatory molecule, PD1 homologue (PD-1H) in human monocyte/macrophages is sufficient to induce spontaneous secretion of multiple cytokines. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
97
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(105 citation statements)
references
References 21 publications
6
97
0
1
Order By: Relevance
“…For example, spontaneous cytokine production was found in monocytes from HIV-infected individuals that overexpressed VISTA. Furthermore, these monocytes were able to increase cytokine production by HIV-specific T cells (15). Investigators in our laboratory have shown that VISTA functions as a ligand on myeloid cells to suppress T cell activation through a putative VISTA receptor (9,10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, spontaneous cytokine production was found in monocytes from HIV-infected individuals that overexpressed VISTA. Furthermore, these monocytes were able to increase cytokine production by HIV-specific T cells (15). Investigators in our laboratory have shown that VISTA functions as a ligand on myeloid cells to suppress T cell activation through a putative VISTA receptor (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…VISTA shares homology with PD ligand 1 and PD-1 (9,12) and can suppress T cell activation in vitro (9). Recently, VISTA was shown to affect the activities of myeloid cells as a receptor (15), and a very recent study showed involvement of VISTA in the uptake of apoptotic cells (13). These data suggest that VISTA activities could exert a profound effect on the development and progression of lupus.…”
mentioning
confidence: 99%
“…HIV results in a shift from “classical” CD14++CD16− to “non-classical” CD14+CD16+ and “intermediate” CD14++CD16+ monocytes, which are associated with an inflammatory phenotype [4042] and greater viremia and/or CD4+ T cell depletion [42, 43]. High expression of the PD1 homologue (PD-1H), which is associated with increased production of TNF, IL-1β, and IL-6, may also contribute to the pro-inflammatory state of these monocytes [44]. CD16+ non-classical and intermediate monocytes have a high migratory capacity, which has been attributed to expression of the chemokine receptors CCR2, CCR5, [45, 46] and CX3CR1 [47].…”
Section: Specific Immunologic Pathways That Predict Disease In Hiv Inmentioning
confidence: 99%
“…Several immunological features play a crucial role in causing progression to AIDS of which chronic immune activation is the most prominent reason [2,3]. It is characterized by increased proinflammatory cytokines; increased expression of T cell activation or exhaustion markers like CD38 and HLA-DR, Programmed Death-1 (PD-1), Tim-3, CTLA-4 and newly described immune regulator PD-1 Homologue (PD-1H) that may interfere with on-going HIV specific cell responses [4][5][6][7]. It is now believed that levels of chronic immune activation predict the progression to AIDS independently from viral loads or CD4 + T lymphocyte counts.…”
mentioning
confidence: 99%
“…Blocking of negative regulatory molecules like PD-1 has received considerable attention due to partial restoration of immune functions upon modulation of these receptors [6]. Recently a new member of PD-1 family called PD-1 Homologue (PD-1H) was implicated to play an important role in pro inflammatory cytokine secretion and enhancing immune responses to HIV antigens [7].…”
mentioning
confidence: 99%